Processing of ceramics (Part I) (New York, 1996)
The book provides a welth of information about the processing of ceramics, including: microsructural targets for ceramics, process control in the manufacture of ceramics, chemical preparation of powders, characterization of partiples and powders, die pressing and isotactic pressing, slip-casting and filter-pressing, tape-casting, injection molding, single cristals, green microstructures and their characterization
Keywords: ceramics,strength of materials